OP02 Sweacp: a structured conversation-based advanced care planning approach in the ACP-naïve swedish context. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Henriksson, M; Helgesson, G; Tishelman, C
Abstract : Background: Sweden has no systematic advance care planning (ACP), nor judicial means of recognizing proxies in end-of-life (EoL) situations. In the SweACP project in the DöBra research program, we focus on engaging stakeholders in active conversations about preferences for future EoL care, rather than using a document-driven approach to ACP. We describe results of feasibility testing a structured conversation-based ACP approach among older adults in the general public as well as exploring their strategies for reasoning about their EoL preferences. Methods: After initial testing in pilot focus groups, a Swedish version of GoWish cards, DöBra cards, and Eco-mapping were used to catalyze discussions on what and who matters at the EoL. The 65 participants from across Sweden actively contacted the researchers volunteering to participate, after receiving information through national patient-or retiree organizations. Both quantitative and qualitative data were analyzed, using descriptive statistics and inductive analysis. Results: DöBra cards were positively received by participants; there was great individual variation in card prioritization and formulation of wild cards. Eco-mapping was met with less enthusiasm but was useful in depicting a social context often taken-for-granted. Qualitative analysis revealed several strategies for reasoning about future EoL care. Conclusions: Having a hands-on tool rather than just talking, and wild cards to open up conversations on possibly taboo subjects were noted strengths of DöBra cards, which also influenced participants' reasoning by shifting focus from hypothetical scenarios to more specific situations. We found the cards to be a feasible tool for stimulating person-centered conversations on EoL preferences.